Hubungan Sosial Ekonomi dan Pola Asuh Ibu dengan Status Gizi Anak Balita di Kelurahan Dapu – Dapura Wilayah Kerja Puskesmas Benu-Benua Kota Kendari Tahun 2017 - Dhesa, Desiderius Bela; Triani, Aisyiah (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Socio-Economic and Parenting is an indirect factor causing malnutrition in children under five. Based on the Ministry of Health of the Republic of Indonesia nationally, the prevalence of nutritional status of children under five according to the combined indicators of TB/U and BB/TB in Indonesia in 2013 was short thin 2.5%, short-normal 27.4%, short fat 6.8%, normal-thin 9.6%, normal-normal 48.6%, and normal-fat 5.1% (Ministry of Health of the Republic of Indonesia, 2013). This study aims to determine the relationship between socio-economic and parenting patterns with the nutritional status of children under five in the Dapu-dapura sub-district, the working area of ​​the Benu-benua health center. This type of research is descriptive analytic with the design (design) using a cross sectional study. This research was carried out June 17-10 July 2017. The population in the study amounted to 359 pregnant women. The sample in this study was 78 pregnant women who were taken by simple random sampling. Collecting data using a questionnaire. This study was analyzed using the Chi Square test with the results showing that there is a socio-economic relationship with the nutritional status of children under five, p value = 0.001. There is a relationship between parenting style and nutritional status of children under five, p value = 0.000. The results of the study can be concluded that it is necessary to educate health workers about the dangers of under-five malnutrition and how to prevent it so that mothers and families can better understand and behave about nutritional status in under-fives.